(untitled) (Journal of Hama University, 2021)
The quality of life of people is affected by their health status. Diabetes is a disease that greatly affects the quality of life of patients; the objective of this descriptive study was to identify the quality of life of patients with diabetes who were treated with insulin. The sample included 100 diabetic patients receiving insulin treatment. They were selected in the covieunt sample. The data were collected using a pre-prepared questionnaire by researcher for this purpose. The study showed that 60% of patients had a good lifestyle according to diet. And that 56% of them have a moderate quality of life related to the drug, and only 8% of them have a good quality of life related to sport and social activity. The researcher recommended that health education be provided about the appropriate sport for diabetics. And the design of educational programs planned on scientific basis according to the actual needs of patients and life.